Assessing the Effect of Strategic Communication Used by Information Service Department on Rural Development - A Study of Sogakofe Community in the Volta Region of Ghana - Yormesor, Edem (UniMAC-GIJ, 2019)
The study investigated the effect of strategic communication used by the Information Services Department using Sogakofe as a case study. One hundred and twenty (120) respondents were selected using convenience and purposive sampling techniques. The study adopted a quantitative research approach in analysing the study findings where a structured questionnaire was used to gather primary data. The first objective was to identify and examine the communication strategy mostly used by the Information Services Department within Sogakofe Township. Descriptive statistics was used to analyse this objective and the study revealed that Cinema Van was the most used communication approach used by the department. Apart from Cinema Van, radio strategy was the second most used approach by the department. The second objective sought to identify the challenges facing the Information Services Department in the Sogakofe Township. Frequency distribution table was used and the result of the study revealed that lack of finances was the major challenge facing the department. Also, the second major challenge facing the department was poor audience engagement and lack of well-developed ICT infrastructure. The last objective was to assess the effect of strategic communication on rural development. Multiple regressions was used to analyse this objective and the results from the study revealed that effective communication, effective collaboration and effective policy implementation all had a positive effect on rural development with the exception of the use of right instrument which had a negative effect on rural development. The study further recommends that more education should be given on the importance of strategic communication to all staff of the Information Services Department across the country as it is the best approach to help develop rural communities.
Thesis